Tc-Labeled Cyclic RGD Peptides for Noninvasive Monitoring of Tumor Integrin αβ Expression - Yang Zhou; Young-Seung Kim; Sudipta Chakraborty; Jiyun Shi; Haijuan Gao; Shuang Liu (Molecular Imaging)
This report describes the biologic evaluations of [ 99m Tc(HYNIC-3P-RGD 2 )(tricine)(TPPTS)] ( 99m Tc-3P-RGD 2 : 6-hydrazinonicotinyl; 3P-RGD 2 = PEG 4 -E[PEG 4 -c(RGDfK)] 2 ; PEG 4 = 15-amino-4,7,10,13-tetraoxapentadecanoic acid; and TPPTS = trisodium triphenylpho-sphine-3,3′,3“-trisulfonate), [ 99m Tc(HYNIC-3G-RGD 2 )(tricine)(TPPTS)] ( 99m Tc-3G-RGD 2 : 3G-RGD 2 = G 3 -E[G 3 -c(RGDfK)] 2 and G 3 = Gly-Gly-Gly), and 99m TcO(MAG 2 −3G-RGD 2 ) (MAG 2 = mercaptoacetylglycylglycyl) as radiotracers for noninvasive imaging of tumor integrin α v β 3 expression in five xenografted tumor-bearing models. Biodistribution and imaging studies were performed in athymic nude mice bearing U87MG, MDA-MB-435, A549, HT29, or PC-3 tumor xenografts. Immunochemistry was performed using the cultured primary tumor cells and xenografted tumor tissues. It was found that the radiotracer tumor uptake followed the trend U87MG > MDA-MB-435 ≈ HT29 ≈ A549 > PC-3. The total integrin β 3 expression levels followed the general trend: U87MG > MDA-MB-435 ≈ A549~HT29 > PC-3. There is a linear relationship between the radiotracer injected dose per gram tumor uptake and the total integrin β 3 expression levels. On the basis of these, it was concluded that radiotracer tumor uptake is contributed by integrin α V β 3 expressed on tumor cells and activated endothelial cells of the tumor neovasculature. 99m Tc-3P-RGD 2 has the capability to monitor integrin α v β 3 expression in a noninvasive fashion.